2022
DOI: 10.2147/jaa.s348369
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Asthma Control in Adolescents with Severe Asthma After Transitioning to a Specialist Adult Centre: A French Cohort Experience

Abstract: Background The prevalence of severe asthma in adolescents is estimated at 6.7%. Transition to adult health services is a vulnerable period for adolescents where there is a risk of poor treatment adherence and loss to follow-up. Purpose This retrospective study evaluated the maintenance of asthma control in young severe asthmatics, 6 months and 1 year after transition to a specialist adult centre. Methods Patients with severe asthma treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Publication years ranged from 2009 to 2022. Three studies were performed in Sweden ( 33 35 ), one in France ( 36 ), one in Canada ( 37 ) and one in the USA ( 38 ). The studies of Bergström et al, Cohen et al and Dufrois et al described components of a transition program and investigated the impact on a set of clinical outcomes in AYA with asthma; while the other three studies described the challenges experienced by AYA with asthma during the transition period ( 35 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication years ranged from 2009 to 2022. Three studies were performed in Sweden ( 33 35 ), one in France ( 36 ), one in Canada ( 37 ) and one in the USA ( 38 ). The studies of Bergström et al, Cohen et al and Dufrois et al described components of a transition program and investigated the impact on a set of clinical outcomes in AYA with asthma; while the other three studies described the challenges experienced by AYA with asthma during the transition period ( 35 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies of Bergström et al, Cohen et al and Dufrois et al described components of a transition program and investigated the impact on a set of clinical outcomes in AYA with asthma; while the other three studies described the challenges experienced by AYA with asthma during the transition period ( 35 38 ). Three studies are cohort studies ( 33 , 34 , 37 ), one study is a quasi-experimental study ( 36 ) and two are qualitative studies ( 35 , 38 ). The age range of included patients varied from 14 to 27 years ( 33 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last assessment in this study, the intervention group scored significantly lower on the Mind the Gap scale than the control group, which supported H3 of the study. In previous studies, it was determined that the difference between the care which adolescents with chronic diseases received with a transition coordinator and a transition plan and the care they expected decreased, and their care satisfaction levels increased 31,32 . While adolescents diagnosed with asthma who achieve a successful transition from pediatric care to adult care can become independent young adults, those who cannot achieve this may experience treatment incompliance and care dissatisfaction as young adults 6 …”
Section: Discussionmentioning
confidence: 99%
“…increased. 31,32 While adolescents diagnosed with asthma who achieve a successful transition from pediatric care to adult care can become independent young adults, those who cannot achieve this may experience treatment incompliance and care dissatisfaction as young adults. 6 In particular, increasing the healthcare transition readiness of adolescents diagnosed with asthma will increase their self-efficacy in terms of asthma management skills.…”
Section: Mind the Gapmentioning
confidence: 99%
“…Further epidemiological studies support the idea that atopy and sensitization to environmental allergens are associated with severe pediatric asthma [ 30 , 31 ]. More recently, Durfois et al, evaluating the maintenance of asthma control during the transition to adult centers in a cohort of adolescents with severe asthma, reported that 80% had allergic asthma and allergic multimorbidities and were partially controlled during follow-up [ 32 ]. In an attempt to characterize severe asthma worldwide, additional data from the International Severe Asthma Registry showed that 50% of patients with severe asthma had high IgE levels (>150) and that IgE levels varied according to severity; patients receiving Global Initiative for Asthma step-five treatment had higher total IgE levels compared to those receiving step-four treatment [ 33 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%